Titin, a Central Mediator for Hypertrophic Signaling, Exercise-Induced Mechanosignaling and Skeletal Muscle Remodeling - Krüger, Martina; Kötter, Sebastian (Frontiers in Physiology, 2016)
Titin is a giant scaffold protein with multiple functions in striated muscle physiology. Due to the elastic I-band domains and the filament-like integration in the half-sarcomere titin is an important factor for sarcomere assembly and serves as an adaptable molecular spring that determines myofilament distensibility. Protein-interactions e.g., with muscle ankyrin repeat proteins or muscle LIM-protein link titin to hypertrophic signaling and via p62 and Muscle Ring Finger proteins to mechanisms that control protein quality control. This review summarizes our current knowledge on titin as a central node for exercise-induced mechanosignaling and remodeling and further highlights the pathophysiological implications.